A protocol integrating aptamer based magnetic separation and gentle dsDNAse cleavage for exosomes isolation and multi-exosomics analysis - Sun, Feifei; Jiang, Xiaofei; Shi, Jiachen; Zhang, Yu; Liu, Xiangyang; Liu, Yuanfa; Tan, Chin Ping; Chen, Mingquan; Xu, Yong Jiang (Elsevier, 2026)
Background: Exosomes, as key mediators of intercellular communication, are increasingly implicated in the pathogenesis of various diseases. Multiomics investigations have uncovered functional roles of low-molecular-weight biomolecules in exosomes. However, conventional methods for isolating exosomes from biological matrices are time-consuming and laborious, limiting the sample preparation for multiomics analysis. Results: We proposed an innovative approach termed as multi-exosomics, which integrates a rapid isolation protocol and multiomics for simultaneous analysis of exosomal metabolites and proteins. In the isolation protocol, the aptamer-functionalized magnetic beads (MBs) targeting CD63 protein were employed to capture exosomes, and dsDNAse was used to isolate purified exosomes. The protocol exhibited high sensitivity, specificity and anti-interference ability, with a detection limit of 1.3 × 104 particals/μL, and recovery rates ranging from 82.52 to 95.13 %. The entire isolation process was completed within 70 min. After isolation, exosomes were dissolved in methanol, ultrasonicated and centrifugated, the supernatant was collected for metabolite extraction, while the sediment was solubilized in denaturant for protein extraction. The simultaneous processing reduces sample consumption and potential bias. The proteins and metabolites identified in the proposed method showed high overlap with those obtained by the ultracentrifugation method. Significance: In conclusion, multi-exosomics provides a rapid and effective platform for exosome isolation and multiomics analysis. Its successful application in clinical samples highlights its excellent feasibility and potential for facilitating the biology research in exosomes.